A single-arm phase II clinical trial of anlotinib combined with chemotherapy for the treatment of metastatic triple-negative breast cancer - Huang, Jia-Yi; Xie, Xiao-Feng; Chen, Xue-Lian; Zhang, Qiu-Yi; Chen, Li-Ping; Bai, Xue; Lan, Xiao-Feng; Song, Lin; Guo, Jin-Feng; Du, Cai-Wen (Frontiers in Oncology, 2023)
Background: Anlotinib is a novel oral small-molecule tyrosine kinase inhibitor (TKI), which can inhibit angiogenesis. The purpose of this study was to evaluate the efficacy and safety of anlotinib combined with chemotherapy in patients with metastatic triple-negative breast cancer (TNBC). Methods: This phase II clinical trial included 40 patients with metastatic TNBC who had previously received anthracycline and/or taxane treatment. All patients received anlotinib combined with chemotherapy. The primary endpoint was progression-free survival (PFS). The secondary endpoints included overall survival (OS), objective response rate (ORR), clinical benefit rate (CBR), disease control rate (DCR) and safety. Results: During May 1, 2019 and April 30, 2022, there were 40 patients enrolled in this study. The median PFS and median OS were 8.8 months (95% confidence interval [CI] 6.5-11.1 months) and 19.0 months (95% CI, 12.1–25.9 months), respectively. The ORR, CBR and DCR were 40.0% (16/40), 85.0% (34/40) and 95.0% (38/40), respectively. Cox univariate and multivariate analyses demonstrated that having more than 3 metastatic sites (p = 0.002; p = 0.020) was an independent and meaningful unfavorable prognostic factor for PFS. 37.5% of patients had grade 3 to 4 treatment-related adverse events (TRAEs). The grade 3 to 4 TRAEs included neutropenia (22.5%), leukopenia (20.0%), secondary hypertension (10.0%), hand-foot syndrome (5.0%), vomiting (5.0%), proteinuria (5.0%) and thrombocytopenia (2.5%). None of the patients withdrew from the study or died due to TRAEs. Conclusion: In this single-arm study, the treatment of metastatic TNBC with anlotinib combined with chemotherapy showed certain efficacy, and its toxicity was acceptable.